Arbitraje con ADRs: un estudio de caso sectorial para empresas de Colombia, México, Brasil y Chile (2011)
This research continues the paper “Generalidades de los ADRs: Un estudio de casosectorial para empresas de Colombia, Mexico, Brasil y Chile” [ADRs generalities: a sectorial case study for companies in Colombia, Mexico, Brazil and Chile]. It is organizedin two sections. The first one covers the unique price theory and the efficient markets hypothesis. In the second one, arbitrage conditions with ADRs are empirically evaluated. The objective is to prove the existence of price differentials between stocks and ADRs, which would allow investors to obtain a risk free return. (Resumen no disponible en español)